Modification of ITU-R rain fade slope prediction model based on satellite data measured at high elevation angle - Hassan Ali, Dao; Islam, Md. Rafiqul; Khalid, Khateeb (IIUM Press, 2011)
Rain fade slope is one of fade dynamics behaviour used by system engineers to design fade mitigation techniques (FMT) for space-earth microwave links. Recent measurements found that fade slope prediction model proposed by ITU-R is unable to predict fade slope distribution accurately in tropical regions. Rain fade measurement was conducted in Kuala Lumpur (3.3̊ N, 101.7̊ E) where located in heavy rain zone by receiving signal at 10.982 GHz (Ku-band) from MEASAT3 (91.5̊ E) on 77.4̊ elevation angle. The measurement has been carried out for one year period. Fade slope S parameter on ITU-R prediction model has been investigated. New parameter is proposed for the fade slope prediction modeling based on measured data at high elevation angle, Ku-band.